Does cognitive flexibility enhance decision-making in sports? - Burhan Başoğlu; Erdil Keyf; Mustafa Vural; Mehmet Gül; Abdullah Doğan; Fatih Karakaş; Gökhan Arıkan; Furkan Çamiçi (Journal of Men's Health)
Background: Decision-making is a multifaceted process crucial in both individual and organizational settings, particularly in high-pressure environments like sports. Cognitive flexibility plays a vital role in enhancing athletes’ decision-making abilities. This study examines the relationship between cognitive flexibility and decision-making processes among athletes, focusing on the sub-dimensions of “Alternatives” and “Control”. Methods: A quantitative research design utilizing a relational survey model was employed. Data were collected from 743 male athletes across various sports disciplines in Türkiye. The Sports Effective Decision-Making Scale and the Cognitive Flexibility Inventory were used as measurement tools. Confirmatory factor analysis confirmed their validity and reliability in the sports context. Regression analysis was conducted to examine the predictive relationships between cognitive flexibility sub-dimensions and decision-making effectiveness. Results: Regression analysis revealed significant findings. The “Alternatives” dimension positively predicted effective decision-making in sports, particularly in external decision-making scenarios (β = 0.207, t = 5.427, p < 0.001). In contrast, “Control” was a stronger determinant of intrinsic decision-making (β = 0.210, t = 5.607, p < 0.001). The R2 values indicated that cognitive flexibility factors explained 18.1% of the variance in effective decision-making and 10.9% in intrinsic decision-making, highlighting the need to explore additional contributing factors. Conclusions: These findings provide practical implications for coaches and sports psychologists. Coaches can enhance athletes’ decision-making abilities by fostering a sense of control and offering diverse alternatives in training and competition. Sports psychologists may develop interventions to strengthen cognitive flexibility and perceived control among athletes. The study emphasizes the necessity of a broader framework for understanding decision-making, suggesting that future research should explore the interplay of emotional, social and cultural factors in athletic decision-making.